Sophie Treadwell y la cuestión racial: el difícil equilibrio entre tradición e innovación / Sophie Treadwell and the Racial Question: The Difficult Balance between Tradition and Innovation - Miriam López Rodríguez (Asparkía, 2013)
Resumen